Effect of geometrical parameters and use of porous material in a Helmholtz resonator on suppression of thermo-acoustic instabilities. Issue 2 (June 2023) - Deshmukh, Nilaj N.; Ansari, Afzal; Degwekar, Sharvil; Paul, Benson; Unnikrishnan, Rohit
Thermo-acoustic instabilities are mainly formed due to in-phase superposition of non-uniform heat release and pressure variation in the combustors of gas turbines, rocket engines and other acoustically confined spaces. These instabilities not only damage the structural system but also reduce its combustion efficiency and heat transfer rate. Hence suppression of thermo-acoustic instabilities is a prominent requirement for stable and safe heat generation in the combustors. In this work, the Helmholtz resonator has been used to suppress the instability. The efficacy of the resonator has been further increased by the addition of absorptive material to it. This work concentrates on inspecting the influence of cavity volume, neck length and neck diameter of the Helmholtz Resonator and the thickness of the absorptive material in the damping process of thermo-acoustic instabilities. The experimentation was carried out for various combinations of resonator cavity volume, neck diameter and neck length, and the best combination was found to be 6 mm neck diameter with 20 mm neck length at 60% volume which provided an acoustic damping of around 30 dB. Further, it was noticed that the addition of absorptive material is effective at lower volumes of Helmholtz resonator, and with an increase in thickness of absorptive material beyond a certain limit, the damping ability of the resonator reduces.